Experiences of women with physical disabilities in labor and delivery assistance - Camila Fernandes da Silva Carvalho; Luciana Pedrosa Leal; Rebeca Paes Barreto Ponce de Leão Vasconcelos Amorim; Cleide Maria Pontes (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To understand the meaning attributed by women with physical disabilities to the health care received and expected during labor and delivery. Methods: Qualitative study, based on Social Network Theory, conducted through an online workshop in April 2022, with the participation of six women with physical disabilities. Data, collected through the focus group technique, underwent thematic content analysis with the assistance of the IRaMuTeQ tool. Results: Three thematic categories emerged: Challenges experienced during pregnancy; The experience within the maternity ward; and, The importance of social networks. The assistance provided by healthcare professionals sometimes differed between what was expected and what was received by women with physical disabilities during labor and delivery. Final Considerations: Experiences were predominantly negative, resulting from inappropriate professional conduct due to ableist attitudes. Support from members of social networks is crucial for preventing stressors.